Psychological Foundations of Educating in the Family - Mahrus As’ad; Agung Alamsyah (STAI Hubbulwathan Duri, 2022)
This research article aims to explore the involvement of parents in educating children in the family. The research approach used is research qualitative with phenomenological methods. Data collection uses interviews with open-ended questions through the zoom meeting and video calls through WhatsApp. The respondents in this study consisted of three parents with different age ranges and professions. The results showed that all respondents agreed that educating children in the family must be based on the provision of religious understanding in every activity that children do. Respondents are always directly involved with children in nurturing and educating children, in terms of accessibility, respondents always supervise children in the process of parenting and education and respondents are responsible for the psychological well-being of each family member, especially their children.